Assessing the Effects of Locus of Control and Work Conflict on Civil Servant Performance: Evidence from the Type Madya Pabean A Customs Office in Pasuruan - Hidayatullah, Ali; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Public services rely on the competence and performance of civil servants, whose actions shape the efficiency and reliability of organizational outcomes. This study examines how locus of control and workplace conflict influence employee performance at the Type Madya Pabean A Customs Office in Pasuruan, Indonesia. Locus of control, representing individuals’ belief in their ability to influence results, fosters initiative, accountability, and proactive work behavior. Meanwhile, workplace conflict, emerging from miscommunication, differing expectations, or job pressures, can either hinder or enhance performance depending on its management. A quantitative explanatory approach was applied, involving 43 employees selected through simple random sampling. Data were collected using structured questionnaires and analyzed via multiple linear regression in SPSS 23. The study ensured that all assumptions were satisfied before analysis. Findings reveal that employees with a strong internal locus of control consistently outperform others, while conflict, if addressed constructively, has a modest but significant positive effect on performance. When considered together, these two factors explain 60.2% of the variance in employee performance. These results underscore the importance of combining personal psychological strengths with effective conflict management strategies to enhance productivity. The study contributes to theory by linking internal dispositions with organizational challenges, and it provides practical guidance for management, emphasizing empowerment, communication, and structured conflict resolution. Overall, cultivating both self-driven initiative and a constructive approach to workplace disagreements is crucial for sustaining high performance and promoting excellence in public sector organizations.